-p+6p=6+2p

Simple and best practice solution for -p+6p=6+2p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -p+6p=6+2p equation:


Simplifying
-1p + 6p = 6 + 2p

Combine like terms: -1p + 6p = 5p
5p = 6 + 2p

Solving
5p = 6 + 2p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-2p' to each side of the equation.
5p + -2p = 6 + 2p + -2p

Combine like terms: 5p + -2p = 3p
3p = 6 + 2p + -2p

Combine like terms: 2p + -2p = 0
3p = 6 + 0
3p = 6

Divide each side by '3'.
p = 2

Simplifying
p = 2

See similar equations:

| -5(1-6r)=30-5r | | 0=t-12+3 | | 14-v=16 | | (7q+3)(4q+1)=0 | | 7x+6y=-14 | | 2m=3(m-10) | | 4(y-2)=29 | | 20-z=1 | | 7=7y+2 | | 9-4x=2+6 | | 5(x-2)+2(X+2)=10-2X | | r+3+12=-1 | | 20-2=1 | | 4x+1+2x+6x-10=180 | | 5n-4n+n-2=20 | | 14=0.1x+7 | | 4x-3(y-2)=15ty | | -4/1= | | 6w-1=8w+7 | | 7k=5 | | 17-y=0 | | x+.0507x=1012 | | -12s-30=-7s | | 4a+2p-2a+4p= | | 100+4x=100 | | x^4+8x^3+18x^2-8=0 | | 5c=7y+6 | | 3m+6-2m=-23 | | 3b+5=2b | | -16.7v-1.41=-16.6v | | 7x-9x=5 | | -19.9p+15.01-4p=1.21-10.1p |

Equations solver categories